Complex giant arteriovenous and lymphatic malformation of the abdominal wall - Oona Tomiê Daronch; Camila Fachin; Bárbara D'Agnoluzzo Moreira; Renato da Silva Freitas; Miguel Ângelo Andrade; Karin Aparecida Becker; Luiz Fernando Tosi; Isabela Picolotto Moraes; Luiz Paulo Rigolon (Elsevier, 2020)
Introduction: Vascular malformations can be congenital or traumatic, the former being the most common and resulting from the unregulated vascular development during the embryogenic period. They can be classified as fast or slow-flow congenital malformations, with arteriovenous malformations being in the first group. It is rare when it happens in childhood and are associated with the lymphatic component. Case report: Girl, 6 years old, with nodulation of growth in the region of the anterior chest-abdominal wall until close to the spine. Angiotomography showed a mass volume of parts, next to the hemithorax wall and left flanks, suggestive of a mixed (lymphatic) component. After undergoing surgical resection of the lesion, she had good evolution, with satisfactory follow-up. Discussion: Vascular malformations are most commonly diagnosed in childhood. Lymphatic malformations are a type of vascular malformation that can cause rare anomalies and, despite their benign nature, can infiltrate different planes of adjacent tissues. Surgical resection is not always possible due to the nature of the lesion; however, when it is performed, it can be curative. Conclusion: The arteriovenous malformations of mixed components are rare. Also, they should be discussed in a multidisciplinary manner among the surgical specialties and can have good results when properly diagnosed and treated.